The Legality of Abortion by Medical Personnel for Rape Victims in Indonesia: A Perspective from Maqashid Sharia by al-Syatibi and al-Tufi - Nur Azizah; Mhd. Syahnan; Budi Sastra Panjaitan (Jurnal Madania)
This research aimed to analyze the legality of abortion by medical professionals for rape victims in Indonesia through the perspective of maqashid sharia. This study adopts a normative legal research approach, utilizing statutory interpretation (legal approach) and conceptual analysis (conceptual approach). The results of this study suggest that maqashid sharia emphasizes that abortions should not be performed arbitrarily and are only permissible in urgent situations that fulfill sharia objectives. This includes scenarios where the mother's life is at risk or serious medical conditions prevent the continuation of pregnancy. Such decisions should be made carefully, considering maslahah and mafsadat and involving consultations with medical experts and religious authorities. The maslahah principles elucidated by al-Tufi expand the flexibility in legal interpretation, allowing for Islamic law adaptation to contemporary needs and conditions. This is particularly relevant in abortion cases, where explicit guidance may not always be found in religious texts. Overall, the maqashid sharia approach to abortion underscores the importance of principles of justice, balance, and humanity in Islamic law. By considering all these aspects, Islamic law can provide relevant and adaptive guidance in addressing contemporary issues like abortion while remaining faithful to the primary objectives of sharia to achieve collective good and avoid harm.